Realizing Social Justice: East Kalimantan's Gender Profile 2023 in the Perspective of Human Rights and Citizenship - Ali Gilang Pratama Ali Gilang Pratama; Suryaningsi; Wingkolatin (HUMANISMA : Journal of Gender Studies, 2024)
This study examines gender inequality in East Kalimantan using a mixed-methods approach that combines quantitative indicators with qualitative insights. Quantitative data from the 2023 Human Development Index (HDI), Gender Development Index (GDI), and Gender Empowerment Index (GEI), supported by education, health, employment, and political participation statistics, reveal persistent disparities between men and women across districts. While aggregate indicators suggest “high” development, women continue to face disadvantages in accessing education, decent work, health services, and decision-making roles. Qualitative evidence, derived from 15 key informant interviews and participatory observations, illustrates the lived realities of these gaps, including early school dropout, maternal health risks, and gender-based violence limiting opportunities. The findings show that more than half of voters are women, yet their legislative representation averages only 16%. The study underscores that gender-responsive development policies are essential to achieve social justice and sustainable equality in provincial governance.